2012
DOI: 10.1111/j.1744-313x.2012.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in interleukin‐18 and interleukin‐28B with Hepatitis B recurrence after liver transplantation in Chinese Han population

Abstract: Interleukin-18 (IL-18) is a potent proinflammatory cytokine, which can promote hepatitis B virus clearance. The latest studies find that genetic polymorphisms near the IL-28B gene are strongly associated with sustained viral response and spontaneous viral clearance in patients with chronically infected hepatitis C and hepatitis B. We investigated the effect of rs187238 and rs1946518 in IL-18 gene and rs8099917 in IL-28B gene on HBV recurrence in liver transplant patients. A total of 200 liver transplant recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Some studies have shown no correlation with the outcomes of HBV infection and responses to treatment [28,29]. Some studies stated that the allele G of rs8099917 was associated with hepatitis B-related hepatocyte injury and reinforced antiviral therapy [24,30,31]. In this study, a significant difference was observed between the responder and non-responder groups both in univariate and multivariate analyses (Table III, p = 0.013).…”
Section: Discussionsupporting
confidence: 41%
“…Some studies have shown no correlation with the outcomes of HBV infection and responses to treatment [28,29]. Some studies stated that the allele G of rs8099917 was associated with hepatitis B-related hepatocyte injury and reinforced antiviral therapy [24,30,31]. In this study, a significant difference was observed between the responder and non-responder groups both in univariate and multivariate analyses (Table III, p = 0.013).…”
Section: Discussionsupporting
confidence: 41%
“…Bao et al also revealed that the polymorphisms at -607 promoter region were not associated with HCC in an HBV-infected Chinese population (6). The -137 and -607 promoter polymorphisms in the IL-18 gene also were not associated with HBV recurrence in the liver transplant patients (39).…”
Section: Il-18 Gene Polymorphisms and Chbmentioning
confidence: 96%
“…As listed before, several studies evaluated the correlation of HLA-DQ rs7453920 with HBV susceptibility, [6,7,914] but quite conflicting results were obtained. To clarify this obscure association, we reappraised this experiment and found that HLA-DQ rs7453920 was not related to HBV susceptibility ( P  > .05).…”
Section: Discussionmentioning
confidence: 99%